Aplikasi Transformasi Reduction to Pole (RTP) Menggunakan Matlab dalam Pengolahan Data Magnetik WDMAM pada Wilayah Tapal Kuda -Jawa Timur - Supriyadi (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2023)
In the magnetic method, the anomalous magnetic field is caused by a dipole magnetic field source. The magnetic anomaly map is complex and relatively challenging to read because each place has a different angle of inclination and declination. The use of a RTP filter is crucial to overcoming the difficulty in magnetic data interpretation. The RTP transformation has been successfully implemented and applied to the WDMAM magnetic data for Tapal Kuda Region-East Java, using the built-in Matlab algorithms. The RTP application in this region uses the values of the inclination angle I = -32.82° and the declination angle D = 0.72°. According to the RTP results' magnetic anomaly, there has been a change in the magnetic field's range from (-345.51 nT to 282.30 nT) to (-975.37 nT to 782.38 nT). The locations of the closures of the positive and negative magnetic anomalies also changed. The middle to northern portions of the Tapal Kuda Region are dominated by a positive magnetic anomaly that is assumed to be related to the Quaternary Volcanic Zone. The positive anomaly closures moved toward the west, specifically toward Mount Bromo and Mount Argopuro. The Horseshoe Region's southern edge is dominated by a negative magnetic anomaly that is assumed to be associated with the Southern Mountain Zone. The negative anomaly closure also shifted location, to the southwest, approaching Mount Semeru..